2003
DOI: 10.1177/1120672103013009-1007
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Intraoperative Antibiotics in Irrigating Solutions on Aqueous Humor Contamination and Endophthalmitis after Phacoemulsification Surgery

Abstract: Intraoperative antibiotic irrigation decreases aqueous humor contamination during phacoemulsification. Further studies are warranted to determine the interrelationship between aqueous humor contamination and endophthalmitis in eyes with posterior capsular rupture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 29 publications
1
47
0
1
Order By: Relevance
“…A prospective study demonstrated that the addition of moxifloxacin drops had no significant effect in the preoperative reduction of conjunctival bacterial colonization above the effect of povidoneiodine 5% alone (Halachimi-Eyal et al, 2009). Antibiotics in the irrigating fluid for cataract surgery have been reported to reduce anterior chamber bacterial contamination rates significantly but their effect on endophthalmitis prevention is less convincing (Sobaci et al, 2003;Srinivasan et al, 2008). The reported lack of effectiveness of both vancomycin and gentamicin in the irrigation fluid may be due to the requirement of more than 140 minutes to exhibit bactericidal effect, whereas the half-life of antibiotics in the anterior chamber is only 51 minutes (Gritz et al, 1996).…”
Section: Prophylaxismentioning
confidence: 99%
“…A prospective study demonstrated that the addition of moxifloxacin drops had no significant effect in the preoperative reduction of conjunctival bacterial colonization above the effect of povidoneiodine 5% alone (Halachimi-Eyal et al, 2009). Antibiotics in the irrigating fluid for cataract surgery have been reported to reduce anterior chamber bacterial contamination rates significantly but their effect on endophthalmitis prevention is less convincing (Sobaci et al, 2003;Srinivasan et al, 2008). The reported lack of effectiveness of both vancomycin and gentamicin in the irrigation fluid may be due to the requirement of more than 140 minutes to exhibit bactericidal effect, whereas the half-life of antibiotics in the anterior chamber is only 51 minutes (Gritz et al, 1996).…”
Section: Prophylaxismentioning
confidence: 99%
“…Alguns dos métodos de profilaxia já foram descritos: iodopovidona imediatamente antes do procedimento, uso de antibióticos imediatamente antes do procedimento, uso de antibióticos depois do procedimento e combinações destes métodos com diferentes formas de administração (subconjuntival, intracameral, tópico) (1,3,4) . As quinolonas de quarta geração estão disponí-veis no mercado há dois anos e apresentam espectro de ação duplo contra bactérias gram-negativas e gram-positivas, incluindo as bactérias mais comuns detectadas como causas de endoftalmite após cirurgia de catarata (5) .…”
Section: Introductionunclassified
“…All four studies randomized participants, but random sequence generation and allocation concealment were described fully only in ESCRS 2007. Hence, we cannot judge whether some selection bias may have occurred in the Christy 1979, Christy 1986and Sobaci 2003 studies.…”
Section: Quality Of the Evidencementioning
confidence: 99%
“…In the study judged as having a high risk of bias, eyes of participants for which the surgical procedure was modified according to physician discretion during surgery were excluded from the study (Sobaci 2003). Reasons for modifying the protocol included administering subconjunctival antibiotics and adding a suture.…”
Section: Risk Of Bias In Included Studiesmentioning
confidence: 99%